The Political Activity of Mazovian Dukes between the 13 th and 15 th Century - Waldemar Graczyk (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
According to some historians, Mazovia once had a separate political existence, with a different form of economy, a social structure and customs that differedfrom those of the Crown, a separate dialect, and its own laws. One of theoutward expressions of its separate existence was its own dynasty. To defend its independence, Mazovia entered into feudal contracts with Bohemia and Kazimierz III the Great. Mazovian dukes also paid homage to Władysław Jagiełło, not only as an acknowledgment of dependence, but also of certain obligations the dukes took upon themselves. After the death of Władysław Jagiełło, a group of Lesser Poland lords proposed the candidature of Siemowit V as king of Poland, and Mazovia had a chance to play a more significant role in Polish politics. It should be stressed that while Siemowit IV still enjoyed popularity on the political scene, his sons, particularly after they divided their patrimony among themselves in 1434, very soon lost significance. The period of the greatest regional disintegration of Mazovia began and the province soon lost any political significance.